Tingkat Kepuasan Konsumen dan Faktor-Faktor yang Memengaruhi Pembelian Pempek NR di Kota Bandar Lampung: Consumer Satisfaction Levels and Faktors that Influence Pempek NR Purchases in Bandar Lampung City - Febby Wulandari; Yaktiworo Indriani; Maya Riantini (Journal of Agriculture and Social Development, 2022)
Pempek is a culinary food favored by many ages, which is processed using the basic ingredients of sea fish and tapioca flour. This study aims to determine the level of customer satisfaction, and the purchasing pattern of pempek NR in the city of Bandar Lampung. The study used a survey method with direct interviews using a questionnaire at the locations of Pempek NR Telukbetung and Rajabasa branches. Data collection in June-July 2020. The research data were analyzed descriptively qualitatively using the Customer Satisfaction Index (CSI) and Important Performance Analysis (IPA) methods. Data collection used accidental sampling of 50 consumers with criteria of at least 17 years and had bought pempek NR twice in the last 3 months before covid-19. The results of research on the level of customer satisfaction are in the criteria of satisfaction with a value of 78.35 percent. The buying pattern is seen from the frequency, namely (62%) buying 5-10 pieces in one transaction, the most popular type is cheese filled pempek (34%), with the purchasing frequency (78%).